Perceived contributory factors to medication administration errors (MAEs) and barriers to self-reporting among nurses working in paediatric units of selected referral hospitals in Rwanda - Nkurunziza, Aimable; Chironda, Geldine; Mukeshimana, Madeleine (International Journal of Research in Medical Sciences, 2018)
Background: Medication administration errors (MAEs) occur in health care settings however, the types, contributing factors to MAEs and barriers to reporting are not well studied in Rwandan context. Methods: Quantitative approach was adopted. Descriptive cross-sectional design was used. A convenience sampling was used to select 151 nurses working in the paediatric units of the selected teaching hospitals in Rwanda. Pre-tested questionnaire for validity and reliability was used to collect data. Data was coded and entered into SPSS version 21. Descriptive statistics and inferential statistics (Chi-square test) were used to analyze data. Results: Approximately 33.6% of the participants were able to identify one type, 17.4 % two, 18.1% three, 17.4% four types, 10.7% six types and only 2.7% identified all the seven MAEs. Identified main contributory factor to MAEs was the heavy workload it like this-Identified main contributory factor to MAEs was the heavy workload [82 (55%)]. The main barrier to self-reporting was fear to be blamed if something happens to the patient as a result of the medication administration error (88 (59.1%)). All the socio demographic were associated with the types of MAEs committed by participants. In addition, the experience, marital status and job position of the participants were significantly associated with factors contributing to MAEs (p= .001, p=.000 and p= .044) respectively whereas all the socio demographic were significantly associated with barriers to self reporting. Conclusions: Factors contributing to MAEs were found in both parties and barriers to self-reporting were identified to be the fear reasons and administrative reasons. Therefore, the heavy workload should be addressed to reduce MAEs and a non-punitive environment is imperative in encouraging self-reporting of MAEs.